Assessment of oral problems and dental status of autistic children in comparison to a matched group of non-autistic healthy children in Benghazi, Libya. - Elamami, Najat M.; Alamami, Najma M. (Libyan Journal of Science &Technology, 2025)
Purpose: The aim of this study is to assess oral problems and the dental status of autistic children in comparison to a matched group of non-autistic healthy children in Benghazi, Libya. Patients and Methods: A cross-sectional comparative study included 60 (38 males, 22 females) children with autism and a control group consisting of 60 healthy children, selected from relatives of the autistic patients in an attempt to match the two groups concerning age, sex, and general dental care background. Both groups were recruited and examined in a rehabilitation center for Autism spectrum disorder ASD children in Benghazi, Libya. The age of children in both groups ranged from 4-14 years. Oral problems involving oral infections, eruption patterns, developmental dental anomalies, and tooth fractures were all assessed clinically while; bruxism assessment was based on the attrition shown on enamel surfaces of all teeth. Dental caries, gingival health, and oral hygiene status were assessed using dmft/DMFT index, Gingival Index (GI), and Plaque Index (PI), respectively. Results were tabulated and statically analyzed using a t-test or (Mann-Whitney) for quantitative variables or variables not normally distributed. Similarly, comparison, as regards qualitative variables, will be done using chi-square, Fisher exact, or Monte Carlo correction as indicated. Results: No statistically significant differences were presented between both groups, as regards oral infection (P=0.097), eruption pattern (P=0.428), tooth fracture (p=0.119), and developmental dental anomalies (p=0.381). However, there was a statistically significant difference between autistic and non-autistic children with respect to attrition due to bruxism (p<0.001), More enamel attrition was observed in autistic children (26.7% vs 1.7%). On the other hand, the mean dmft score was lower in children with autism than in controls (5.23 vs. 4.06; P < 0.001) these differences were not statistically significant. Moreover, children with autism revealed moderate levels of gingivitis and dental plaque compared to their control group with no statistically significant (p=0.188),(p= 0.157) respectively. Conclusions: children with autism in Benghazi experienced moderate levels of attrition and gingivitis, and their caries level was lower than their counterparts. Therefore, oral health education programs should be planned to provide appropriate preventive protocol as well as effective treatment for this special section of society.